Comparison of Patient-Reported Quality of Life Following Direct-to-Implant Prepectoral and Subpectoral Breast Reconstruction Using BREAST-Q: A Randomized Controlled Trial - Dyrberg, Diana L; Dalaei, Farima; Sollie, Martin; Bille, Camilla; Koudahl, Vibeke; Sørensen, Jens A; Thomsen, Jørn B (Archives of Plastic Surgery, 2024)
Background Direct-to-implant breast reconstruction (DIR) is becoming more and more accepted. There is a lack of high-quality studies assessing differences in patient-reported quality of life (QoL) between different implant placement methods. The aim of this randomized controlled (clinical) trial was to compare QoL between women reconstructed by sub- or prepectoral implant placement.Methods We included women over 18 years eligible for DIR. Patients were randomly assigned to reconstruction by subpectoral or prepectoral implant placement. Assessment of QoL and patient satisfaction was made using the BREAST-Q questionnaire for postmastectomy breast reconstruction and compared between the sub- and prepectoral reconstructed groups preoperatively and after 3 and 12 months of follow-up.Results A total of 42 women were allocated to sub- or prepectoral reconstruction with 21 patients in each group. There were no differences in patient characteristics between groups. Regarding all the selected BREAST-Q scales: (1) satisfaction with the reconstructed breast, (2) satisfaction with the breast implant, (3) satisfaction with the overall outcome, (4) psychosocial well-being, (5) sexual well-being, and (6) physical well-being—we found no significant differences between the two groups. Assessing each group independently we found, that in both groups sexual well-being improved after surgery postoperatively compared to the preoperative scores.Conclusion We found high satisfaction and QoL following both sub- and prepectoral breast reconstruction. We found no significant differences between groups suggesting both methods for DIR can be used. Despite our high-quality data, a larger sample size and longer postoperative follow-up are needed to further investigate the differences in QoL between sub- and prepectoral breast reconstruction.
Keywords: breast reconstruction; quality of life; BREAST-Q; breast implant; patient-reported outcome